How Ready Are the Turkish Hospitality and Travel Organizations for E-Complaint Handling? - Özlem Aşman Alikılıç; Ferika Özer Sarı (Online Academic Journal of Information Technology, 2016)
Main purpose of this study was to examine Turkish hospitality and travel organizations’ readiness level with e-complaint handling processes and to reveal their return intent to e-complaints. Although handling customer complaints online has become a strategic concern in hospitality and travel industries, we couldn’t attain any studies which compare sub categories of services in the context of e-complaints. Hence, the secondary aim was to contribute to the literature in this field. Data were collected from the online Turkish complaint site “Sikayetimvar.com” which has made customer feedback publicly available. For the airline sector 299 and for health-care sector 316 filed complaints were transferred into single documents as data for content analysis. Each dataset was coded. Then coded data were analyzed by using SPSS. Findings indicate that health-care and airline companies were more enthusiastic about a response than the lodging sector. Results of the paper bring up some implications for lodging sector.